Industrias culturales en el Ecuador: un sector de crecimiento y desarrollo económico - Daniel Flores, José (Editorial Uniagustiniana, 2018)
This chapter seeks to highlight some of the hypothe-ses about the contribution of cultural and creative in-dustries to the growth and economic development of nations. The authors show the recognition advances of cultural industries in the context of a dynamic sector of the Ecuadorian economy. Thus, the chapter starts reflecting on the concept of cultural and creative activ-ities as part of a strategic and productive sector as well as of an activity that generates an intangible value of symbolic wealth, which leads to a process of revaluation and recognition of these industries as transversal axes of targeted public policies in the economic develop-ment generation. Findings show that it is necessary to review some stablished elements in the national agenda from studies based on opportunities generation in the fields of cinematography, music, publishing, performing arts and design. The existing relations between growth, economic development and culture are gathered from a theoretical review, in order to study some statistical collected data in relation to the analyzed country.